Dialumene as a Dimeric or Monomeric Al Synthon for C–F Activation in Monofluorobenzene - Liu, Xufang; Dong, Shicheng; Zhu, Jun; Inoue, Shigeyoshi (Journal of the American Chemical Society, 2024)
The activation of C–F bonds has long been regarded as the subject of research in organometallic chemistry, given their synthetic relevance and the fact that fluorine is the most abundant halogen in the Earth’s crust. However, C–F bond activation remains a largely unsolved challenge due to the high bond dissociation energies, which was historically dominated by transition metal complexes. Main group elements that can cleave unactivated monofluorobenzene are still quite rare and restricted to s-block complexes with a biphilic nature. Herein, we demonstrate an Al-mediated activation of monofluorobenzene using a neutral dialumene, allowing for the synthesis of the formal oxidative addition products at either double or single aluminum centers. This neutral dialumene system introduces a novel methodology for C–F bond activation based on formal oxidative addition and reductive elimination processes around the two aluminum centers, as demonstrated by combined experimental and computational studies. A “masked” alumylene was unprecedentedly synthesized to prove the proposed reductive elimination pathway. Furthermore, the synthetic utility is highlighted by the functionalization of the resulting aryl-aluminum compounds.